Reducing Reconfiguration Overheads in Heterogeneous Multicore RSoCs with Predictive Configuration Management. (4th October 2009) - Chevobbe, Stéphane; Guyetant, Stéphane
Abstract : A predictive dynamic reconfiguration management service is described here, targeting a new generation of multicore SoC that embed multiple heterogeneous reconfigurable cores. The main goal of the service is to hide the reconfiguration overheads, thus permitting more dynamicity for reconfiguring. We describe the implementation of the reconfiguration service managing three heterogeneous cores; functional results are presented on generated multithreaded applications.